Model Pemanfaatan TikTok untuk Pengembangan Bisnis Digital Wirausahawan Muda di Kota Surakarta - Santi Rochmawati; Suranto Suranto (Jurnal Simki Economic, 2026)
The use of the TikTok application in digital business development is increasingly important along with changes in consumer behavior and the development of digital marketing. This study aims to analyze the use of the TikTok Application as a medium for digital business development by young entrepreneurs in the city of Surakarta. The research uses a qualitative approach with a case study design, with data collection techniques through in-depth interviews, observations, and documentation. Data analysis is carried out using an interactive analysis model which includes data reduction, data presentation, and conclusion drawn. The results of the study show that TikTok is not only perceived as an entertainment platform, but has been utilized as a strategic digital promotional medium to expand market reach, build brand awareness, and improve interaction with consumers. TikTok's utilization strategy is adaptive and adjusted to the characteristics of the product, target market, and marketing strategies applied. Interaction through comments, DMs, and features live streaming plays an important role in building two-way communication and consumer trust. However, the effectiveness of TikTok utilization is influenced by differences in product characteristics, content strategies, and the ability of business actors to adapt to changes in the platform's algorithm. This research contributes to the development of digital entrepreneurship literature by presenting contextual empirical evidence of how young entrepreneurs reinterpret TikTok from just an entertainment platform to a strategic digital marketing media. The findings of this research enrich the theoretical discourse on the adaptation of digital entrepreneurship and short video platform-based marketing strategies in a local business context. Practically, this research provides implications for young entrepreneurs in optimizing the utilization of digital platforms through adaptive content strategies and orientation towards interaction quality.